1984
DOI: 10.1002/app.1984.070290531
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of poly(ϵ‐caprolactone) (PCL) and poly(styrene‐co‐acrylonitrile) (SAN) blends. I. Blends containing SAN with 24 wt% acrylonitrile

Abstract: SynopsisPolymer blends of poly(ecapro1actone) (PCL) and poly(styrene-co-acrylonitrile) (SAN), containing 24 wt 9% acrylonitrile (AN), were prepared, and their transition behavior was examined by thermal analysis and dynamic mechanical testing. The blends were judged to be compatible on the basis of the presence of a single, compositionally dependent glass transition. The results of thermal treatment upon blend glass transition behavior and the dependence of thermal history upon the crystallization of semicryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 29 publications
0
15
0
2
Order By: Relevance
“…Therefore, it is very imethylene-propylene-diene terpolymer. portant for the development of rubber-modified SAN can readily blend with a number of other polymers to find how to improve the impact polymers including poly(1-caprolactone), 3,4 polystrength without deterioration of the other propcarbonate, [5][6][7][8][9] poly(vinylidenefluoride), 10 nylon, …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very imethylene-propylene-diene terpolymer. portant for the development of rubber-modified SAN can readily blend with a number of other polymers to find how to improve the impact polymers including poly(1-caprolactone), 3,4 polystrength without deterioration of the other propcarbonate, [5][6][7][8][9] poly(vinylidenefluoride), 10 nylon, …”
Section: Introductionmentioning
confidence: 99%
“…PCL/SAN blends. Various works reporting prepa ration and application of PCL/SAN polymer blends have been documented since 1982 [84][85][86][87]. The com patibility of PCL/SAN polymer blends has been inves tigated by various research groups.…”
Section: Polycaprolacton Systemsmentioning
confidence: 99%
“…The com patibility of PCL/SAN polymer blends has been inves tigated by various research groups. Chiu and Smith [84] have reported compatibility of PCL/SAN blends over the entire range of blend compositions using DSC and a dynamic mechanical analyzer. They have found that PCL is compatible with SAN containing AN con tents which are greater than 8 wt % but less than 28 wt %.…”
Section: Polycaprolacton Systemsmentioning
confidence: 99%
“…CPE can be blended as impact modifier for brittle SAN to improve mechanical properties. Many studies have been reported to improve the compatibility that results the final mechanical properties of SAN by blending with other polymers including nylon [5], poly(phenylacrylate) [6], polyvinyl chloride (PVC) [7,8], poly carbonate [3,9], poly(caprolactone) [10][11][12], polypropylene [13]. Compatibility is a technical term defining the property profile of the blend in view of a certain application and, it is a function of the interaction of polymer molecules in the blend and can be detected using various methods including mechanical and interfacial measurements.…”
Section: Introductionmentioning
confidence: 99%